JOINT DESIGN AND MOTION RESEARCH OF ENTERTAINMENT ANTHROPOMORPHIC ROBOT - LIAO WeiQiang; ZHAO ChangMing; MA WenShu; ZENG DeChang (Jixie qiangdu)
Joint design and motion research is key to the design and research of entertainment Anthropomorphic robot,It direct impact on attitude and balance of robot motion. So,we focus on research Joint structure design and joint movement. Joint of robot hand and foot is designed by human engineering principle and finite element analysis method. Solution of joint position and velocity is obtained base on establishing joint coordinates and calculation. Effective solve robot movement in the process of stability with analysis of the balance of motion. Find a way to achieve robot walking,turning and lateral movement and other humanoid movements by the study the effect of the slip and calculation of the sliding force. A fixed frequency current control method is proposed,and realized robot key gait planning.